Pengaruh Kinerja Keuangan Perusahaan Terhadap Devidend Payout Ratio - Gean Karlos Purba, Iwan Firdaus, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
This research was conducted to examine the effect of Currrent ratio (CR), Return on asset (ROA), Debt to Equity Ratio (DER) and Sales Growth to Dividend Payout Ratio (DPR). The object for this research is pharmaceutical and cosmetics sub-sector Â listed on the Indonesia Stock Exchange in the period 2012-2016. This research was conducted using quantitative menthod with total 30 sample of research were determined by saturated sampling. Method of hypothesis testing using t-test. This research use Currrent ratio (X1), Return on asset (X2), Debt to Equity Ratio (X3), Sales Growth (X4) as independent variable and Dividend Payout Ratio as dependent variable. The results of this research is Return on asset positive and has significant effect to Dividend Payout Ratio, for Currrent ratios and Sales Growth a positive but significant effect on Dividend Payout Ratio, Â whlile the Debt to Equity Ratio positive and has no significant effect to Dividend Payout Ratio.